RESPON UNI EROPA TERHADAP PEMISAHAN DIRI CATALUNYA DARI SPANYOL TAHUN 2017 - Ramadhana, Pebrianta; Iskandar, Irwan (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2019)
This study discusses "The European Union's Response to the Separation of Catalunya from Spain". Separation of territory is the formation of a new political unit which is carried out through the separation of the elements of sovereignty of a country. Catalunya, one of the regions of Spain, wants to leave the territory of Spain and form a country called the Republic of Catalonia. Political, cultural, economic and other issues are the cause for the departure of Spain from Catalunya. The method used in this research is Qualitative Explanatory. This study uses secondary data, namely by using library research. This study uses the Pluralism Perspective by Paul R, Viotti and Mark V.Kauppi, Level of Group Behavior Analysis, and International Organizational Theory by Clive Archer.The results of this study are that the European Union and the International World do not recognize the independence referendum carried out by Catalunya and still recognize Catalunya as a sovereign territory of the Spanish State. The referendum is considered illegal. The European Union requested that Spain be able to resolve its internal problems well in its country.Â Keywords: Secession, Independence, Referendum, Separatism, Response